Arf, Sec7 and Brefeldin A: a model towards the therapeutic inhibition of guanine nucleotide-exchange factors. (26th October 2005) - Zeghouf, M.; Guibert, B.; Zeeh, J.-C.; Cherfils, J.
Abstract : GEFs (guanine nucleotide-exchange factors), which stimulate GDP dissociation from small G-proteins, are pivotal regulators of signalling pathways activated by small G-proteins. In the case of Arf proteins, which are major regulators of membrane traffic in the cell and have recently been found to be involved in an increasing number of human diseases, GDP/GTP exchange is stimulated by GEFs that carry a catalytic Sec7 domain. Recent structural results captured snapshots of the exchange reaction, revealing that Sec7 domains secure Arf-GDP to membranes before nucleotide exchange takes place, taking advantage of a built-in structural device in Arf proteins that couples their affinity for membranes to the nature of the bound nucleotide. One of the Arf–Sec7 intermediates was trapped by BFA (Brefeldin A), an uncompetitive inhibitor of Arf activation that has been instrumental in deciphering the molecular principles of membrane traffic at the Golgi. BFA targets a low-affinity Arf–Sec7 intermediate of the exchange reaction. It binds at the Arf-GDP/Sec7 interface, thus freezing the complex in an abortive conformation that cannot proceed to nucleotide dissociation. In the cell, this results in the specific inhibition of Arf1 by a subset of its GEFs, and the efficient and reversible block of membrane traffic at the Golgi. The mechanism of BFA leads to the concept of 'interfacial inhibition', in which a protein–protein interaction of therapeutic interest is stabilized, rather than impaired, by a drug. Up-regulated activity of small G-proteins is involved in various human diseases, making their GEFs attractive candidates to interrupt specifically the corresponding signalling pathway. Interfacial inhibitors are proposed as an alternative to competitive inhibitors that may be explored for their inhibition.